Synthetic BiOBr/Bi2S3/CdS Crystalline Material and Its Degradation of Dye under Visible Light - Yunhan Jin; Zhe Xing; Yinhui Li; Jian Han; Heike Lorenz; Jianxin Chen (Crystals, 2021)
Constructing heterojunction has attracted widespread concerns in photocatalysis research. BiOBr/Bi2S3/CdS composite material with a sea urchin shape was directly obtained by first synthesizing BiOBr microspheres. The morphology, structure and composition of the composite material were characterized by XRD, EDX, SEM and XPS. Dye degradation experiments showed that 83.3% of methylene blue removal was achieved after 2 h of visible light irradiation. The reaction rate under optimal conditions was 0.014 min−1 and the photocatalytic degradation process follows a pseudo-first-order kinetic model. Based on the EPR test results, the main active species involved in the reaction were •O2− and h+. The conduction band and valence band edge potential calculations confirmed the key role of CdS in the production of •O2−.